2012 International Conference on Speech Database and Assessments 2012
DOI: 10.1109/icsda.2012.6422454
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of English narrow focus production by L1 English, Beijing and Taiwan Mandarin speakers

Abstract: L1 English and two varieties of L1 Mandarin English speech data were extracted from the Taiwan AESOP corpus (Asian English Speech cOrpus Project) for the purpose of investigating differences in the realization of English narrow focus by L1 speakers of North American English, Taiwan Mandarin and Beijing Mandarin. Results show the combined effect of two patterns of L2 focus production: general underdifferentiation of on-focus and post-focus contrasts, which was exhibited by both L2 speaker groups, and transfer o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
3
1

Relationship

1
9

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 12 publications
1
5
0
Order By: Relevance
“…Other specific features found in both Taiwan and Beijing L2 English include underdifferentiation of narrow-focus and onfocus/no focus contrasts [5,6]. Similar underdifferentiation patterns were obtained in PVI analyses of Vietnamese Australian L2 English speech rhythm [7].…”
Section: Introductionsupporting
confidence: 63%
“…Other specific features found in both Taiwan and Beijing L2 English include underdifferentiation of narrow-focus and onfocus/no focus contrasts [5,6]. Similar underdifferentiation patterns were obtained in PVI analyses of Vietnamese Australian L2 English speech rhythm [7].…”
Section: Introductionsupporting
confidence: 63%
“…In a production study of TM-speaking and BM-speaking learners of English, Visceglia et al [2] found mixed patterns of L1 transfer. In their English productions TM speakers showed reduced duration on post-focal materials, and both TM and BM speakers exhibited compression of post-focal intensity.…”
Section: L2 Acquisition Of Focus Prosodymentioning
confidence: 99%
“…Compared to F0, the effect of intensity on prosody is not understood well. Visceglia et al (2012) reports that L1 English speakers raised the intensity on focus words more robustly compared to L2 English of Mandarin speakers, suggesting that their L1 use of acoustic correlates of focus may be transferred to L2 English. As for Japanese focus prosody, Lee and Xu (2012) found that the distribution of the intensity is similar to F0, in that the focus words should carry higher intensity and the pre-focus and post-focus words lower it.…”
Section: Measurementmentioning
confidence: 99%